Does Lipid Profile Affect Thrombin Generation During Ramadan Fasting in Patients With Cardiovascular Risks?. (November 2017) - Sassi, Mouna; Chakroun, Taher; Chouchène, Saoussen; Hellara, Ilhem; Boubaker, Hamdi; Grissa, Mohamed Habib; Khochtali, Ines; Hassine, Mohsen; Addad, Faouzi; Elalamy, Ismail; Nouira, Semir
There is evidence that diet and variation in lipid metabolism can influence blood coagulation, but little is known about the effect of Ramadan fasting on plasmatic coagulation pattern. We investigated the effect of Ramadan fasting on thrombin generation (TG) in patients with cardiovascular disease (CVD) risks, and we aimed to assess the effect of lipid profile on TG parameters. The study was conducted in 36 adults having at least 2 CVD risks and in 30 healthy controls. Coagulation pattern was assessed by both classical clotting times and TG test. A complete lipid profile was performed simultaneously. Patients were invited 2 times: 1 week before Ramadan and during the last week of the Ramadan. The TG parameters were not different in patients with CVD risks compared to healthy controls. Fasting had no effect on plasmatic coagulation parameters and on TG profile. Individual analysis of the mean rate index (MRI) of TG revealed 3 groups: group 1 with no modification of MRI, group 2 with a significant increase in MRI (81.64 nM/min vs 136.07 nM/min; P < .001), and group 3 with a significant decrease in MRI (125.27 nM/min vs 73.18 nM/min; P = .001). Only in group 2, a significant increase was observed in total cholesterol and low-density lipoprotein cholesterol. Changes in lipid profile during Ramadan fasting did not influence the global coagulation pattern in patients with CVD risks. Whereas, a significant increase in the propagation phase of TG was associated with a significant increase in cholesterol levels, which was not found with the other TG parameters.